2008
DOI: 10.1016/j.virusres.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Murine leukemia virus reverse transcriptase: Structural comparison with HIV-1 reverse transcriptase

Abstract: Recent X-ray crystal structure determinations of Moloney murine leukemia virus reverse transcriptase (MoMLV RT) have allowed for more accurate structure/function comparisons to HIV-1 RT than were formerly possible. Previous biochemical studies of MoMLV RT in conjunction with knowledge of sequence homologies to HIV-1 RT and overall fold similarities to RTs in general, provided a foundation upon which to build. In addition, numerous crystal structures of the MoMLV RT fingers/palm subdomain had also shed light on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 75 publications
0
49
0
Order By: Relevance
“…Structural differences may also play a role in the observed decrease in RNase H activity for the gammaretroviral enzymes. Both the MoMLV and XMRV RTs exist as monomers, unlike the heterodimeric HIV-1 RT, which benefits from the additional support provided by the p51 subunit (17). An additional difference in nucleic acid binding includes the longer distance between the polymerase and RNase H active sites in XMRV RT than in HIV-1 RT (1 bp or approximately 3.4 Å) (28,76).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural differences may also play a role in the observed decrease in RNase H activity for the gammaretroviral enzymes. Both the MoMLV and XMRV RTs exist as monomers, unlike the heterodimeric HIV-1 RT, which benefits from the additional support provided by the p51 subunit (17). An additional difference in nucleic acid binding includes the longer distance between the polymerase and RNase H active sites in XMRV RT than in HIV-1 RT (1 bp or approximately 3.4 Å) (28,76).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 RT is structurally very different from the gammaretroviral MoMLV RT, which is closely related to XMRV RT in sequence and presumably in structure (17,28,29,61). HIV-1 RT exists as a heterodimer composed of two subunits: an enzymatically active 66-kDa p66 domain, which contains the polymerase domain (composed of the fingers, palm, thumb, and connection subdomains) and the RNase H domain, and a 51-kDa p51 domain, which mainly provides structural support and has an amino acid sequence identical to that of p66 but does not contain the RNase H domain, which is removed by proteolytic cleavage (38,45,72,75,79).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, fragments 4, 5, and 8 and analogs 13 and 17 tended to have similar potency for HIV-1 and MoMLV RT. Although the sequence similarity between HIV-1 RT and MoMLV RT is low, ranging from 6% in the connection domain to 25% in the fingers and palm subdomains, both viral RTs have similar folding arrangements in their polymerase domains (31). The conformational landscape of the binding sites may therefore be very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis revealed that HIV-1 and MLV RTs are rather different at their thumb and connection subdomains, while their fingers and palm subdomains show significant homology (for a review, see Coté & Roth, 2008). MLV RT is 111 amino acids longer than the p66 subunit of HIV-1 RT.…”
Section: Rtmentioning
confidence: 99%